Multi‐component β‐diversity approach reveals conservation dilemma between species and functions of coral reef fishes. (8th August 2016) - Loiseau, N.; Legras, G.; Kulbicki, M.; Mérigot, B.; Harmelin‐Vivien, M.; Mazouni, N.; Galzin, R.; Gaertner, J.C.
Abstract: Aim: We applied a multicomponent approach based on the decomposition of taxonomic (both presence–absence and abundance) and functional beta diversity to determine the influence of ecological factors in shaping spatial distribution diversity of coral reef fishes, and the implications for conservation decisions. Location: Lagoons of ten atolls characterized by low human pressure but with contrasted geomorphology in the Tuamotu Archipelago, French Polynesia. Methods: We computed beta diversities and their partitioning components, both at local (inter‐transect, from 200 m to 10 km) and large (among atolls, from 22 to 350 km) spatial scales. Null models were applied to test whether the observed beta diversity differed from random expectation. Multiple generalized dissimilarity models were run to test which environmental factors were the best predictors of observed beta diversities. Results: Beta diversity was indistinguishable from randomness at both spatial scales. Species remained generally interchangeable among transects within an atoll and to some extent among atolls. However, strong deviance explained by models showed that the number of species, the number of individuals and functional traits present in transects and atolls were determined by deterministic factors (i.e. environmental factors). Modelling each beta diversity component separately also revealed partial mismatch among atolls and among species and functional dissimilarities. The influence of environmental variables strongly varied among atolls, species and functional dissimilarities. Main conclusions: By revealing the spatial scaling of ecological factors and partial congruence among species and functional diversity, assessment of beta diversity provides insight into conservation planning. Our results support the idea that conservation planning applied to protect taxonomic diversity cannot be fully extended to functional diversity. We have addressed the dilemma of which diversity component should be favoured in conservation strategies.